2003
DOI: 10.1002/jbm.a.10034
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐treated, collagen‐anchored polylactone: Its cell affinity evaluation under shear or shear‐free conditions

Abstract: Poly(L-lactic acid)(PLLA) and poly(L-lactic-co-glycolic acid) (PLGA) (85/15) were modified by plasma treatment. Then they were collagen anchored (PT/CA), and the cell affinity was evaluated by cell culture under shear or shear-free conditions. A convenient and "intuitionistic" dyeing method has been proposed for measuring the modified depth when plasma treatment is applied for the treatment of porous scaffolds. A parallel plate flow chamber was developed in order to study the cell affinity of a material under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…The surface of the NH 3 plasma pretreatment was reported to be easier to anchor collagen. 24,25 Culture of mouse 3T3 fibroblasts demonstrated that the method can effectively facilitate cell migration and that the cultured cells can be distributed evenly throughout the scaffold. These studies disclosed that plasma treatment was helpful in promotion of bioactive macromolecules to the surface of synthesized polymers.…”
Section: 45mentioning
confidence: 99%
“…The surface of the NH 3 plasma pretreatment was reported to be easier to anchor collagen. 24,25 Culture of mouse 3T3 fibroblasts demonstrated that the method can effectively facilitate cell migration and that the cultured cells can be distributed evenly throughout the scaffold. These studies disclosed that plasma treatment was helpful in promotion of bioactive macromolecules to the surface of synthesized polymers.…”
Section: 45mentioning
confidence: 99%
“…Typical surface modification methods include ethanol treatment, 84 alkaline hydrolysis, 85 and plasma oxidization. 86 In plasma oxidization of polystyrene, for example, the outermost surface of the polymer is disrupted and hydrophilic functional groups are produced which can interact strongly with proteins such as fibronectin 87,88 and collagen 89 to improve cell anchorage. Ultimately, a balance between hydrophobicity and hydrophilicity is required for cell attachment through protein adsorption; Groth et al 81 identified the optimal water contact angle as 55-75º based on a fibroblast study.…”
Section: Fibrinmentioning
confidence: 99%
“…Gas plasma or plasma polymerization has been used to modify and functionalize PLGA surfaces (6)(7)(8). The retention of plasma generated functional groups on PLGA surface appears quite weak (9,10), thus making it hard to have targeting molecule conjugation.…”
Section: Introductionmentioning
confidence: 99%